RESPON HARGA SAHAM DI SEKITAR PENGUMUMAN DIVIDEN DI BURSA EFEK INDONESIA - Rahmi Aryanti; Lily Rahmawati Harahap; Ellys Thoyib (Fakultas Ekonomi Universitas IBA, 2022)
This study aims to prove the response of stock prices around the dividend announcement 10 days before and after the ex-dividend date that occurs in 2021. Using a sample of 158 issuers listed on the Indonesia Stock Exchange that declare cash dividends, the results of trend graph analysis and difference tests the average change in stock prices (paired sample t-test) shows that the first; the announcement of cash dividends has caused a tendency for stock price changes to increase before the ex-dividend date and decrease after the ex-dividend date, secondly; there is a significant difference in stock price changes before and after the ex-dividend date. This indicates that there was a significant movement of stock prices during the two observation periods due to the announcement of the dividend distribution.